Calcul interprétatif métaphorique à l'exemple de la structure « Le NI est un N2 » - Domanska-Gruszka, Jolanta (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2006)
In the present paper the author tries to analyze the phenomenon of linguistic metaphor not at the level of 'langue' but rather as the result of discursive uses. The basic predicative structure le NI est un N2 in French in metaphorical use is treated not as categorization but as characterization of subject. The author compares pragma-semantic and discursive approach of the metaphorical predication and its interpretation - analogy as included in the system and 'conformity judgment' as a local characterization. The final considerations are about philosophical implications of metaphorical words uses.
Interpretative metaphoric calculation on the example of the structure of le NI and un N2